Study on the Pattern of Tobacco Usage among the Residents of an Urban Area in Raichur and Factors Influencing Their Intention to Quit Tobacco - Ayesha Siddique Nawaz; Swetha Rajeshwari; Bheemayya Badesab (Medsci Publications, 2018)
Background: About 28.6% of Indian population aged 15 years and above use tobacco in any form. With the pictorial warning on tobacco products, awareness towards tobacco hazards has increased with time but its role alone towards cessation is questionable. This research was conducted to study the pattern of tobacco usage among residents of an urban area and also to know the factors influencing their intention to quit. Methods: This Community based cross sectional study was carried out in the urban area for a period of two months.Data about pattern of tobacco usage and intention to quit was collected from 170 tobacco users aged 15 years and above, using tobacco either in smoking or smokeless form. Results: About 48.2 % of the study subjects smoked tobacco, 42.9 % used smokeless form and 8.8 % used both forms. Education, awareness of health hazards and noticing pictorial warning played vital role in intention to quit Conclusion: Tobacco users unable to quit, despite having intention to quit tobacco should be made aware of Tobacco Cessation Clinic and encouraged to seek help.